MiR-585-5p impedes gastric cancer proliferation and metastasis by orchestrating the interactions among CREB1, MAPK1 and MITF - Wang, Yunwei; Li, Ming; Zeng, Jiaoxia; Yang, Yunshu; Li, Zengshan; Hu, Sijun; Yang, Fangfang; Wang, Na; Wang, Wenlan; Tie, Jun (Frontiers in Immunology, 2022)
Background Gastric cancer (GC) is one of the most malignant and lethal cancers worldwide. Multiple microRNAs (miRNAs) have been identified as key regulators in the progression of GC. However, the underlying pathogenesis that miRNAs govern GC malignancy remains uncertain. Here, we identified a novel miR-585-5p as a key regulator in GC development. Methods The expression of miR-585-5p in the context of GC tissue was detected by in situ hybridization for GC tissue microarray and assessed by H-scoring. The gain- and loss-of-function analyses comprised of Cell Counting Kit-8 assay and Transwell invasion and migration assay. The expression of downstream microphthalmia-associated transcription factor (MITF), cyclic AMP-responsive element-binding protein 1 (CREB1) and mitogen-activated protein kinase 1 (MAPK1) were examined by Immunohistochemistry, quantitative real-time PCR and western blot. The direct regulation between miR-585-5p and MITF/CREB1/MAPK1 were predicted by bioinformatic analysis and screened by luciferase reporter assay. The direct transcriptional activation of CREB1 on MITF was verified by luciferase reporter assay, chromatin immunoprecipitation (ChIP) and electrophoretic mobility shift assays (EMSAs). The interaction between MAPK1 and MITF was confirmed by co-immunoprecipitation (Co-IP) and immunofluorescent double-labelled staining. Results MiR-585-5p is progressively downregulated in GC tissues and low miR-585-5p levels were strongly associated with poor clinical outcomes. Further gain- and loss-of-function analyses showed that miR-585-5p possesses strong anti-proliferative and anti-metastatic capacities in GC. Follow-up studies indicated that miR-585-5p targets the downstream molecules CREB1 and MAPK1 to regulate the transcriptional and post-translational regulation of MITF, respectively, thus controlling its expression and cancer-promoting activity. MiR-585-5p directly and negatively regulates MITF together with CREB1 and MAPK1. According to bioinformatic analysis, promotor reporter gene assays, ChIP and EMSAs, CREB1 binds to the promotor region to enhance transcriptional expression of MITF. Co-IP and immunofluorescent double-labelled staining confirmed interaction between MAPK1 and MITF. Protein immunoprecipitation revealed that MAPK1 enhances MITF activity via phosphorylation (Ser73). MiR-585-5p can not only inhibit MITF expression directly, but also hinder MITF expression and pro-cancerous activity in a CREB1-/MAPK1-dependent manner indirectly. Conclusions In conclusion, this study uncovered miR-585-5p impedes gastric cancer proliferation and metastasis by orchestrating the interactions among CREB1, MAPK1 and MITF.